2016
DOI: 10.3390/molecules21040465
|View full text |Cite
|
Sign up to set email alerts
|

Carnosol and Related Substances Modulate Chemokine and Cytokine Production in Macrophages and Chondrocytes

Abstract: Phenolic diterpenes present in Rosmarinus officinalis and Salvia officinalis have anti-inflammatory and chemoprotective effects. We investigated the in vitro effects of carnosol (CL), carnosic acid (CA), carnosic acid-12-methylether (CAME), 11,12, in murine macrophages (RAW264.7 cells) and human chondrocytes. The substances concentration-dependently reduced nitric oxide (NO) and prostaglandin E 2 (PGE 2 ) production in LPS-stimulated macrophages (i.e., acute inflammation). They significantly blunted gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 40 publications
(70 reference statements)
3
35
0
Order By: Relevance
“…Interestingly, that study showed an important inhibitory effect of carnosol on IL‐6 and PGE2 production . Similar effects have been observed in murine lipopolysaccharide (LPS)‐stimulated macrophages and human IL‐1β‐stimulated chondrocytes confirming a role for carnosol in regulating acute and chronic inflammatory processes …”
Section: Polyphenols In Osteoarthitissupporting
confidence: 73%
“…Interestingly, that study showed an important inhibitory effect of carnosol on IL‐6 and PGE2 production . Similar effects have been observed in murine lipopolysaccharide (LPS)‐stimulated macrophages and human IL‐1β‐stimulated chondrocytes confirming a role for carnosol in regulating acute and chronic inflammatory processes …”
Section: Polyphenols In Osteoarthitissupporting
confidence: 73%
“…As one of the main active diterpene in rosemary, carnosol (CS) has been largely investigated for anti-tumoral, anti-inflammatory and anti-oxidant activities in vitro and in vivo ( Ortuno et al ., 2015 ; Sanchez et al ., 2015 ). In previously studies, carnosol significantly inhibited inflammatory responses such as IL-1β, tumor necrosis factor-α (TNF-α) and increased IL-10 in inflamed mice skin ( Yao et al ., 2014 ; Schwager et al ., 2016 ). Carnosol also inhibited NO generation and expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2) in RAW 264.7 cells and mice skin ( Mengoni et al ., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic diterpene carnosol decreased concentrations of PGE 2 and NO, and reduced gene expression of iNOS, IL-1α, IL-6, and CCL5 in LPSstimulated macrophages. In addition, it interfered with transcription factor NF-κB activation and influenced expression of anabolic and catabolic genes in chondrosarcoma cell line SW1353 and in primary human chondrocytes [86].…”
Section: Herbal Medicinal Products For Topical Use In the Treatment Omentioning
confidence: 99%